Analisis Strategi Pemasaran dalam Meningkatkan Daya Saing pada Usaha Stick Rayco Bunda di Kecamatan Lintau Buo Utara Kabupaten Tanah Datar - Nadila Fitriana; Zulhelmi Zulhelmi (Lembaga Yasin AlSys, 2026)
Although marketing strategies in micro, small, and medium enterprises (MSMEs) have received attention in various studies, studies that specifically discuss marketing strategies in improving the competitiveness of locally based snack food businesses in rural areas remain limited. This study aims to analyze marketing strategies in improving competitiveness at Stick Rayco Bunda Business in Lintau Buo Utara Subdistrict, Tanah Datar Regency. This study employed a qualitative approach with a field research design, involving three participants consisting of the business owner, an employee, and a consumer selected through purposive sampling. Data were collected through interviews, observation, and documentation, and were then analyzed using the Miles and Huberman model. The results showed that the marketing strategy implemented through the marketing mix (product, price, place, and promotion) was able to improve business competitiveness, particularly through product quality and competitive pricing. However, this study also found fluctuations in production and sales during the 2020–2024 period, an increase in the number of competitors, limited labor, and distribution that remained confined to the local market. These findings contribute to the development of marketing mix and MSME competitiveness theory while broadening understanding of marketing strategies in snack food businesses in rural areas. This study concludes that optimizing all elements of the marketing mix is important for improving business competitiveness. Therefore, MSME actors need to improve distribution, promotion, and resource management so that marketing strategies become more effective. The implications of this study include theoretical contributions to enriching the MSME marketing literature and practical contributions for business actors in designing more effective marketing strategies, while also opening opportunities for further research on digital marketing in MSMEs.